Clozapine decreases exploratory activity and increases anxiety-like behaviour in the Wistar-Kyoto rat but not the spontaneously hypertensive rat model of attention-deficit/hyperactivity disorder - Fie, Sarah Mc; McFie, S.; Mc Fie, Sarah; Va, Russell; Sterley, Toni-Lee; Fm, Howells; Howells, Fleur M.; Russell, Vivienne A. (Brain Research, 2012)
The spontaneously hypertensive rat (SHR) is the most widely used animal model of ADHD. SHR has been found to have increased glutamate-stimulated noradrenaline release from varicosities in several brain areas. Besides its effects on dopamine D4 receptors, clozapine, an atypical antipsychotic with antagonistic effects on α(1)-adrenoceptors, may reduce activation of α(1)-adrenoceptors in SHR and thereby attenuate their hyperactivity. The aims of the study were to determine the effect of clozapine (post-natal day (P) 21-P35, 10 mg/kg/day) on SHR and Wistar-Kyoto (WKY), SHR's normotensive control, and a standard laboratory strain, Sprague Dawley (SD). Rat behaviour was assessed in the open field (P32), novel object (P33) and elevated plus maze (P34) tests that measured locomotor and anxiety-related behaviour. An in vitro superfusion technique was used to measure [(3)H]noradrenaline release in prefrontal cortex (PFC) and hippocampal slices (P35 or P36). Clozapine decreased exploratory activity in WKY, consistent with antagonism of dopamine D4 and α(1)-adrenoceptors reducing the behavioural response to novelty. Clozapine also increased anxiety-related behaviour of WKY. However, clozapine did not affect SHR, suggesting that genetic predisposition may play a role in determining clozapine's behavioural effects. WKY have been shown to have higher levels of dopamine D4 receptor expression in the PFC than SHR, which may be a reason for their elevated response to clozapine. SHR released more [(3)H]noradrenaline from PFC and hippocampal slices in response to glutamate- and elevated potassium-stimulation, compared to WKY and SD rats. However clozapine treatment did not affect glutamate-, GABA- or depolarization-evoked release of [(3)H]noradrenaline.